2016
DOI: 10.1371/journal.pone.0154797
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin-2 as an Infection-Related Biomarker to Predict Clinical Outcome in Ischemic Stroke

Abstract: ObjectivesFrom previous data in animal models of cerebral ischemia, lipocalin-2 (LCN2), a protein related to neutrophil function and cellular iron homeostasis, is supposed to have a value as a biomarker in ischemic stroke patients. Therefore, we examined LCN2 expression in the ischemic brain in an animal model and measured plasma levels of LCN2 in ischemic stroke patients.MethodsIn the mouse model of transient middle cerebral artery occlusion (tMCAO), LCN2 expression in the brain was analyzed by immunohistoche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…Circulating lipocalin-2 is filtered in the kidney by the glomeruli, while the protein is captured by the proximal tubular epithelial cells. 30,31 Thus, when injected into the circulation, exogenous lipocalin-2 is enriched in the proximal tubule but does not appear in the urine in large quantities. 26 This is in line with the present findings that serum and urinary lipocalin-2 levels are not significantly correlated with each other in healthy human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating lipocalin-2 is filtered in the kidney by the glomeruli, while the protein is captured by the proximal tubular epithelial cells. 30,31 Thus, when injected into the circulation, exogenous lipocalin-2 is enriched in the proximal tubule but does not appear in the urine in large quantities. 26 This is in line with the present findings that serum and urinary lipocalin-2 levels are not significantly correlated with each other in healthy human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, this up‐regulation was a reversible effect. In rats with traumatic brain injury and transient focal cerebral ischaemia, LCN2 mRNA was significantly up‐regulated during 24 to 72 hours, although it was decreased 1 week or 1 month after injury . These findings imply that LCN2 can be acutely produced and released in the brain after an injury but then decreases after a period of time …”
Section: The Alteration Of Lcn2 Expression Its Receptors and Other Imentioning
confidence: 91%
“…Plasma LCN2 levels were increased in later‐life depressed patients with cognitive disturbance and also in VaD patients . However, a study of stroke patients reported that higher infection rates in acute ischaemic stroke patients could lead to an elevation of circulating LCN2 levels . Another study conducted in VaD patients reported no differences in plasma and CSF LCN2 levels .…”
Section: The Expression Of Lcn2 and Its Receptors In The Brain In Casmentioning
confidence: 94%
See 2 more Smart Citations